Matrix-free hydrodynamic study on the size distribution and conformation of three technical lignins from wood and non-wood - Alzahrani, Qushmua E.; Adams, Gary G.; Gillis, Richard B.; Besong, Tabot M.D.; Kök, M. Samil; Fong, Emily; Harding, Richard A.; van Dam, Jan E.G.; Gosselink, Richard J.A.; Rowe, Arthur J.; Harding, Stephen E. (De Gruyter, 2016)
Molecular weight (MW) and related conformational data of three commercially available technical lignins (Alcell L, kraft L, and soda L) have been studied by means of analytical ultracentrifugation, taking advantage of some recent developments in both sedimentation velocity and sedimentation equilibrium determinations. The lignins were dissolved in dimethyl sulphoxide (with ca. 90% solubility), and solutions were studied with regards to their oligomeric state, heterogeneity profiles (distribution of sedimentation coefficients), and molecular weight distributions (MWD). Alcell L and soda L have similar properties showing one major low MW component and two minor high MW components, whereas kraft L appears to be larger and more uniform, i.e., it shows a more monodisperse MWD. Weight average molecular weight (Mw) data from sedimentation equilibrium obtained by the new SEDFIT-MSTAR procedure in conjunction with MULTISIG analysis were found to be ~18 kDa (Alcell L), 25 kDa (kraft L), and 15 kDa (soda L). Further analysis of the data by means of the routines MULTISIG and M_INVEQ confirmed the presence of additional components in Alcell L and soda L, and the larger size and high degree of monodispersity of kraft L. The intrinsic viscosity data of the three lignins were found to be very similar in the range of 22–24 ml g-1, and all data were consistent with an elongated plate shape molecular structure with an equivalent discoid aspect ratio ~30.